Becoming-evolutionary?: Animal Transformations in Kingsley’s Alton Locke - Ben Moore (Cahiers Victoriens et Edouardiens)
Focusing on Chapter 36 of Charles Kingsley’s novel Alton Locke (1850), where the hero recounts a dream during which he undergoes a series of transformations into various animals, beginning at ‘the lowest point of created life’ as a madrepore or coral, and culminating with the early history of humanity, this article explores the relation between Kingsley’s text and Deleuze and Guattari’s concept of ‘becoming-animal’. It argues that the evolutionary fantasy Alton Locke recounts plays out a tension between the restoration of fixed, ‘molar’ identity and the ‘molecular’ disruption of identity. The relevance of the dream’s origin in pestilence and fever is also considered, as is the repetition of death within the dream. The article concludes by considering the possibility that Kingsley’s text might help formulate a concept of ‘becoming-evolutionary’, building on Deleuze and Guattari.